Checklist of remnant forest fragments of the metropolitan area of Belém and historical value of the fragments, State of Pará, Brazil - Amaral, Dário Dantas do; Vieira, Ima Célia Guimarães; Almeida, Samuel Soares de; Salomão, Rafael de Paiva; Silva, Antonio Sérgio Lima da; Jardim, Mário Augusto Gonçalves (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2009)
In northern Brazil, the metropolitan area of Belém, Pará, harbors the largest urban population in the Amazon with more than two million inhabitants, and retains remnant primary forests occupying less than 400 km2, about 30% of the original coverage. These forests are fragments located on river islands and on continental areas with restricted access such as military bases, public schools and research institutions, and official forest reserves. This study aimed to survey the trees in six major forest fragments, varying in size from 2 to 15 ha, as well as to identify the species most vulnerable of disappearing in the region. These fragments were Amafrutas (15 ha), Trambioca Island (2 ha), city park “Bosque Rodrigues Alves” (15 ha), Combu Island (10 ha), Gunma reserve (10 ha), and Mocambo reserve (5 ha). Forest fragments were surveyed using fixed quadrates of 250 m2 with the inclusion of all trees with Diameter at Breast Height (DBH) ≥ 10 cm at 1,30 m from the soil. The forest inventories registered 759 tree species in 69 families, of which 12 are officially listed as endangered based on the 1992 Brazilian national list (Instruction of the Brazilian Institute of Environment and Natural Resources - IBAMA, September 2008) and the 2008 Pará state list (Decree nº. 802, de 20/02/2008). These species are: Aspidosperma desmanthum Benth. ex Müll. Arg. (Apocynaceae), Cedrela odorata L. (Meliaceae), Eschweilera piresii S.A. Mori (Lecythidaceae), Euxylophora paraensis Huber (Rutaceae), Hymenolobium excelsum Ducke (Leguminosae), Manilkara huberi (Ducke) Chevalier (Sapotaceae), Tabebuia impetiginosa (Mart. ex DC.) Standl. (Bignoniaceae), Mezilaurus itauba (Meisn.) Taub. ex Mez (Lauraceae) e Qualea caerulea Aubl. (Vochysiaceae).